2006
DOI: 10.1074/jbc.m512728200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations of the Ligand-binding Domain of an N-Methyl-d-aspartate Receptor

Abstract: The mechanism of partial agonism at N-methyl-D-aspartate receptors is an unresolved issue, especially with respect to the role of protein dynamics. We have performed multiple molecular dynamics simulations (7 ؋ 20 ns) to examine the behavior of the ligand-binding core of the NR1 subunit with a series of ligands. Our results show that water plays an important role in stabilizing different conformations of the core and how a closed cleft conformation of the protein might be stabilized in the absence of ligands. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 32 publications
5
37
1
Order By: Relevance
“…One possibility is that stabilization of the closed cleft state, not simply rotation of D2 relative to D1, is the chief determinant of efficacy. This hypothesis finds support in many molecular dynamics studies, which report higher relative domain mobility, decreased hinge stability, and increased agonist flexibility with partial agonists (14,16). Numerous structure/function studies have documented the effects of destabilizing cross-cleft interactions in NR2, GluR2, and GluR6, which include increased deactivation rates as well as lower apparent affinity and efficacy (18 -20).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…One possibility is that stabilization of the closed cleft state, not simply rotation of D2 relative to D1, is the chief determinant of efficacy. This hypothesis finds support in many molecular dynamics studies, which report higher relative domain mobility, decreased hinge stability, and increased agonist flexibility with partial agonists (14,16). Numerous structure/function studies have documented the effects of destabilizing cross-cleft interactions in NR2, GluR2, and GluR6, which include increased deactivation rates as well as lower apparent affinity and efficacy (18 -20).…”
Section: Discussionmentioning
confidence: 75%
“…Additionally, introduction of a cleft-stabilizing GluR6 D1D2 interaction into GluR2 dramatically slowed deactivation and increased glutamate sensitivity but had no effect on cleft closure, although GluR6 is almost 6°more closed than GluR2 in the full agonist state (18). Molecular dynamics simulations have also observed ligand movement within the NR1 binding pocket without altering the degree of domain closure (16). It has been suggested that both incomplete and unstable cleft closure have similar effects on single channel gating (20), raising the possibility that the degree of cleft closure may simply be a manifestation of closed cleft stability.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Computer-aided molecular dynamics (MD) simulations that are based on the growing number of LBD structures can be a useful tool to estimate protein fluctuations at physiological temperatures, provided the appropriate caveats are recognized (see section V.A). Such studies have provided hints about permissible intraprotein motions within the LBD during the cleft closure transition as well as interactions at the domain interface (Arinaminpathy et al, 2002;Kaye et al, 2006;Lau and Roux, 2007;Dravid et al, 2010). MD simulations can provide estimates of the stability of the ligand-protein interactions in the binding pocket, adding further detail to our understanding of ligand selectivity and efficacy (Mendieta et al, 2001(Mendieta et al, , 2005Erreger et al, 2005b;Kaye et al, 2006;Pentikä inen et al, 2006;Erreger et al, 2007).…”
Section: Krupp Et Al (1998)mentioning
confidence: 99%
“…Such studies have provided hints about permissible intraprotein motions within the LBD during the cleft closure transition as well as interactions at the domain interface (Arinaminpathy et al, 2002;Kaye et al, 2006;Lau and Roux, 2007;Dravid et al, 2010). MD simulations can provide estimates of the stability of the ligand-protein interactions in the binding pocket, adding further detail to our understanding of ligand selectivity and efficacy (Mendieta et al, 2001(Mendieta et al, , 2005Erreger et al, 2005b;Kaye et al, 2006;Pentikä inen et al, 2006;Erreger et al, 2007). Additional experimental techniques that can test predictions obtained from MD simulations or crystal structures include NMR, ultraviolet or infrared spectroscopy, and fluorescence resonance energy transfer Oswald, 2002, 2004;Cheng et al, 2005;Du et al, 2005;Madden et al, 2005;Valentine and Palmer, 2005).…”
Section: Krupp Et Al (1998)mentioning
confidence: 99%